2016
DOI: 10.1016/j.jclepro.2016.08.070
|View full text |Cite
|
Sign up to set email alerts
|

Toward a better practice for estimating the CO2 emission factors of cement production: An experience from China

Abstract: a b s t r a c t CO 2 emission estimation of cement production is an underlying tool to identify the CO 2 sources, to evaluate the reduction efforts and to set prospective reduction targets for the Chinese cement industry. However, lack of domestic data has limited the reliability and accuracy of CO 2 emission estimation for Chinese cement industry. To develop an accurate and comprehensive CO 2 emission factor for Chinese cement industry, this study established a factory-level database of 197 cement production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(30 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…Note: 1 The value of compressive strength is obtained from the concrete sample of 100 mm × 200 mm (4" × 8") in accordance with ASTM C39/C39M.…”
Section: Amount Of Rap and Associated Compressive Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Note: 1 The value of compressive strength is obtained from the concrete sample of 100 mm × 200 mm (4" × 8") in accordance with ASTM C39/C39M.…”
Section: Amount Of Rap and Associated Compressive Strengthmentioning
confidence: 99%
“…On the other hand, the use of concrete not only consumes the bulk of natural resources but also generates the emission of carbon dioxide (CO 2 ) escalating global warming [1,2]. Thereby, many researchers and engineers have made great efforts to design sustainable concrete mixes by using supplement cementitious materials (SCM) and reclaimed asphalt pavement (RAP).…”
Section: Introductionmentioning
confidence: 99%
“…The intensities of building material are usually non-negative variables and are known to be positively skewed. Therefore, a skewed distribution, such as lognormal, Weibull, or Gamma, might better fit observed data (Cao et al 2016). One hundred forty-six urban residential building project samples, including various kinds of building structure, are collected from the Construction Project Investment Estimation Handbook (Yu and Li 1999).…”
Section: Uncertainties In Materials Intensitymentioning
confidence: 99%
“…Gao et al (2017) found that CO 2 emission factors in China differed from the default CO 2 emission factors recommended by various organizations (CSI, 2011;IPCC, 2006). To improve the accuracy of CO 2 emissions estimates, recent works have amended CO 2 emission factors for the Chinese cement sector (Cai et al, 2016;Cao et al, 2016b;Cui & Liu, 2008;Shen et al, 2016).…”
mentioning
confidence: 99%